AC corrosion behavior and the effect of stone-hard-soil on corrosion process in the earth alkaline rich environment. (May 2022) - Liang, Yi; Du, Yanxia; Chen, Le; Tian, Nianpei; Zhang, Lei; Qiao, Lijie
Highlights: In the earth alkaline rich environment, AC corrosion failure and local corrosion are observed under high CP level and AC interference. Ca(OH)2 and Mg(OH)2 could not act as protective film under high CP level and AC interference due to disturbance of gas evolution. Corrosive environment is created adjacent to coupon surface due to the effect of alternating electric field on Cl - mitigation and the formation of stone-hard-soil. Occurrence and development of local corrosion in the experiment conditions are discussed. Abstract: Many oil and gas pipelines are parallel with high voltage transmission lines in a long distance. Corrosion failures in such situation have been reported and typical corrosion morphology (stone-hard-soil) have found in these failures. In this paper, AC corrosion behavior and the effects on corrosion process after the formation of typical corrosion morphology are investigated in earth alkaline rich environment through laboratory simulated tests. This study produce a corrosion rate map where high CP AC corrosion and local corrosion are observed. In domain of high CP AC corrosion, local environment, including typical morphology of stone-hard-soil and corrosive electrolyte at interface, are analyzed. After the formation of stone-hard-soil, the electric field and its effects on migration of Cl -, are discussed. These results, combining the changes in instantaneous potential and pH at local regions, provide a guide to understand the occurrence and development of local corrosion under high CP level and AC interference.